Empirical investigation on portfolio decision making of individual investors - MS. B. NEERAJA; MR. P. SOBANRAJA (The journal of contemporary issues in business and government, 2020)
The research aim is to assess the Investigation on Portfolio Decision making of Individual Investors. This study helps the investors to make an investment in various kinds of avenues like Mutual funds, Shares, Gold, Saving account, Real estate, Fixed deposit, etc. The Primary purpose of any investor is to limit hazard and maximize return. A sample of 152 employees from various organizations and students by providing the google forms and collecting the real time data and it is used for this analysis. This study helps us to find out to know about the individual preferences on investment, to maximize return on investment, to know the knowledge of investment and to know about the factors considering investment decisions.